2009
DOI: 10.1128/jcm.01756-09
|View full text |Cite
|
Sign up to set email alerts
|

Serum (1-3)-β- d -Glucan as a Tool for Diagnosis of Pneumocystis jirovecii Pneumonia in Patients with Human Immunodeficiency Virus Infection or Hematological Malignancy

Abstract: (1-3)-␤-D-Glucan (BG) reactivity was tested in serum samples from 28 patients with human immunodeficiency virus infection or a hematological malignancy and Pneumocystis jirovecii pneumonia (PCP) and 28 control patients. The sensitivity and specificity of BG detection with the Fungitell assay for PCP were 100 and 96.4%, respectively, using a cutoff value of 100 pg/ml. Serum BG testing looks promising for the noninvasive diagnosis of PCP. Our data suggest that a higher cutoff value for the diagnosis of PCP than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 10 publications
2
84
0
3
Order By: Relevance
“…We have also found that the fungus Pneumocystis is a frequent respiratory colonizer in HIVinfected individuals, particularly in those with COPD (34)(35)(36). (1→3)-b-D-glucan (BG) is a component of fungal cell walls that is shed into the blood and can be detected in the serum of patients with fungal pneumonia (37,38). We have recently found detectable BG levels in HIVinfected adult outpatients without pneumonia, and BG levels correlate strongly with airway obstruction, DL CO , echocardiographic pulmonary artery pressures, higher inflammatory cytokines, increased sputum neutrophils, and activated peripheral lymphocytes (39).…”
Section: Fungi As Possible Agents Of Microbial Translocationmentioning
confidence: 99%
“…We have also found that the fungus Pneumocystis is a frequent respiratory colonizer in HIVinfected individuals, particularly in those with COPD (34)(35)(36). (1→3)-b-D-glucan (BG) is a component of fungal cell walls that is shed into the blood and can be detected in the serum of patients with fungal pneumonia (37,38). We have recently found detectable BG levels in HIVinfected adult outpatients without pneumonia, and BG levels correlate strongly with airway obstruction, DL CO , echocardiographic pulmonary artery pressures, higher inflammatory cytokines, increased sputum neutrophils, and activated peripheral lymphocytes (39).…”
Section: Fungi As Possible Agents Of Microbial Translocationmentioning
confidence: 99%
“…Interestingly, high serum BG levels have been reported in patients with PcP (Desmet et al, 2009;Nakamura et al, 2009;Teramoto et al, 2000). Consistently, such levels decreased with effective anti-Pneumocystis treatment (Teramoto et al, 2000).…”
Section: 3mentioning
confidence: 99%
“…False positive results were reported in patients undergoing bacterial septicemia, hemodialysis with cellulose dialysis membranes, treatment with immunoglobulin, glucan-containing antitumor drugs, amoxicillinclavulanate, piperacillin-tazobactam or contact with gauze or surgical sponges containing BG (Ponton, 2009). Furthermore, since invasive fungal infections induce also an increase of serum BG, the test should often be associated with laboratory assays aiming at detecting such infections (Desmet et al, 2009). These preliminary studies suggest that in the right clinical setting serum BG may provide a useful noninvasive diagnostic adjunct for patients with Pneumocystis infection.…”
Section: 3mentioning
confidence: 99%
“…Therefore this test may be used as non invasive test for diagnosis of PcP 49 , 50 . This test may however not correlate with disease severity and should not be used to monitor patients on treatment 87 .…”
Section: Other Testsmentioning
confidence: 99%